CIVIL MISSIONS OF THE EUROPEAN UNION - THE CASE OF THE EULEX KOSOVO MISSION - Cvetković, Nenad; Kovač, Mitar (Political Review, 2023)
By strengthening its internal strength over the years, the European Union as a supranational organization has shown interest and formed capacities for a stronger foreign policy and security influence on the environment in the last twenty years. The EULEX Kosovo mission was the first real and major test of European security policy in the field of civil affairs and internal security in conflict environments. The rule of law is one of the key civilizational achievements that are not easy to establish in modern societies, as was demonstrated in the case of Kosovo and Metohija, a part of the Republic of Serbia that has been accompanied by decades of security problems for the local population. The analysis of certain indicators that evaluate the rule of law, political stability, corruption and work of judicial and police bodies, indicated that the state of internal security in Kosovo and Metohija has not changed much since the establishment of the EULEX mission. Certain capacities of the temporary authorities in Prishtina in the area of customs, police, and justice have been established, especially in the adoption of the strategic and legal framework, and partly in the creation of adequate material working conditions. On the other hand, the fulfilled formal prerequisites did not produce results in the daily work of the institutions to protect the local population and their human, property, security and other rights. The existence of corruption in the judiciary, police, and customs was registered as a bigger problem, which is connected to the political influence of local authorities and their mutual connections and relations. This is indirectly reflected in the small number of convictions in cases of high corruption and especially organized crime. Kosovo and Metohija still belong to the areas that are highly influenced by organized criminal groups, with the possibility of manifesting terrorism and extremism. The EULEX mission and international forces did not provide the conditions for the return of over 200,000 displaced Serbs, and those who still live in Kosovo and Metohija face the lack of basic security conditions for a normal life. The ideas, principles, and guidelines of the CSDP of the EU have largely failed to be realized within the mission in Kosovo and Metohija for the last 14 years of implementation. There is a need for a detailed analysis by the expert bodies of the EU in order to better prepare and respond to future engagements, and overall to improve the credibility of the EU.